Implikasi Berlatih Yoga Terhadap Daya Tahan Kardiorespirasi Pada Individu dengan Sedentary Lifestyle - I Nyoman Agus Pradnya Wiguna (Jurnal Yoga dan Kesehatan, 2022)
Cardiorespiratory endurance is a component of physical fitness. Having good cardiorespiratory endurance shows the ability of the respiratory system, circulation system and muscle system to work optimally, so that a person can maintain performance without being accompanied by significant fatigue. Yoga has become a popular intervention in various age groups. The purpose of this study was to summarize and examine the results of research related to the implications of practicing yoga on cardiorespiratory endurance in individuals with a sendentary lifestyle. The research method uses a literature review, where research articles are collected from online databases, namely Google Scholar and Pubmed. Inclusion and exclusion criteria were applied to obtain research articles that were original, relevant to the desired topic, published in the last 10 years, the full text was accessible and the research methods and results were well explained and valid. In total there are only 5 articles that qualify for discussion. In this study, 4 studies showed that there was an effect of giving yoga practice on increasing cardiorespiratory endurance, while 1 study showed no effect, this could be due to insufficient exercise intensity to encourage changes in VO2Max, so further research is still needed on giving yoga to increase in cardiorespiratory endurance, and pay attention the intensity of exercise.